Advanced Manufacturing Technologies Modern Machining, Advanced Joining, Sustainable Manufacturing - Gupta, Kapil; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides details and collective information on working principle, process mechanism, salient features, and unique applications of various advanced manufacturing techniques and processes belong. The book is divided in three sessions covering modern machining methods, advanced repair and joining techniques and, finally, sustainable manufacturing. The latest trends and research aspects of those fields are highlighted.
Fabrication of Micro-cutting Tools for Mechanical Micro-machining -- Machining of Glass Materials: An Overview -- Thermal-Assisted Machining of Titanium Alloys -- Abrasive Water Jet Machining of Composite Materials -- Advanced Joining and Welding Techniques: An Overview -- Laser-Based Repair of Damaged Dies, Molds, and Gears -- Friction Stir Welding-An Overview -- Ultrasonic Spot Welding-Low Energy Manufacturing for Lightweight Fuel Efﬁcient Transport Applications -- Perspectives on Green Manufacturing -- Experimental Investigation and Optimization on MQL-Assisted Turning of Inconel-718 Super Alloy -- Dry and Near-Dry Electric Discharge Machining Processes -- Laser Metal Deposition Process for Product Remanufacturing.
Keywords: Manufactures; Sustainability; Ceramic materials; Metals; Machines, Tools, Processes; Sustainability; Ceramics; Metals and Alloys